Faktor-Faktor yang Mempengaruhi Penyerapan Tenaga Kerja di Sektor Pertambangan Kecamatan Batulicin - Mahdalena Mahdalena; Ruddy Syafrudin (PPJP Universitas Lambung Mangkurat, 2022)
This research was conducted to determine: (1) The effect of wages on labor absorption in the coal mining sector in Batulicin District. (2) The effect of production on labor absorption in the Coal Mining sector in Batulicin District. (3) The effect of investment on labor absorption in the Coal Mining sector in Batulicin District. This study uses secondary data related to Production, Investment and Wages, data collection techniques using document data, total sampling techniques from secondary data. Data analysis used multiple linear regression analysis, F test and T test. The results obtained in this study indicate that production has a significant and positive effect on labor absorption in the manufacturing sector in Batulicin District 2010-2019. Investment has a significant and positive effect on employment in the manufacturing sector in Batulicin District 2010-2019. Wages do not have a significant effect and are negatively related to the absorption of labor in the manufacturing sector in Batulicin District 2010-2019. Production, investment and wages, simultaneously have in the manufacturing sector in Batulicin District 2010-2019.